2009
DOI: 10.1002/path.2611
|View full text |Cite
|
Sign up to set email alerts
|

Müller cell‐derived VEGF is a significant contributor to retinal neovascularization

Abstract: Vascular endothelial growth factor (VEGF-A) is a major pathogenic factor and a therapeutic target for age-related macular degeneration, diabetic retinopathy, and retinopathy of prematurity. Despite intensive effort in the field, the cellular mechanisms of VEGF action remain virtually uninvestigated. This situation makes it difficult to design cellular target-based therapeutics for these diseases. In light of the recent finding that VEGF is a potential neurotrophic factor, revealing the cellular mechanisms of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
189
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 34 publications
14
189
1
1
Order By: Relevance
“…These cells develop and maintain a close contact with both superficial vessels and deeper capillaries via their multiple end-feet (Newman and Reichenbach, 1996) and have been implicated in angiogenesis by virtue of their ability to produce angiogenic substances in response to hypoxia (Pierce et al, 1995;Stone et al, 1995;Robbins et al, 1997). However, as the Müller cell-specific deletion of VEGF-A inhibited neovascularization in a mouse model of oxygen-induced retinopathy without affecting physiological vascularization or retinal morphology (Bai et al, 2009), it was assumed that Müller cells play a greater role in proliferative retinopathy than physiological angiogenesis. In our study, the deletion of the sEH in Müller cells clearly affected endothelial cell proliferation as well as Notch signaling and tip cell filopodia formation in mice, indicating that Müller cells make a more important contribution to retinal angiogenesis than generally appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…These cells develop and maintain a close contact with both superficial vessels and deeper capillaries via their multiple end-feet (Newman and Reichenbach, 1996) and have been implicated in angiogenesis by virtue of their ability to produce angiogenic substances in response to hypoxia (Pierce et al, 1995;Stone et al, 1995;Robbins et al, 1997). However, as the Müller cell-specific deletion of VEGF-A inhibited neovascularization in a mouse model of oxygen-induced retinopathy without affecting physiological vascularization or retinal morphology (Bai et al, 2009), it was assumed that Müller cells play a greater role in proliferative retinopathy than physiological angiogenesis. In our study, the deletion of the sEH in Müller cells clearly affected endothelial cell proliferation as well as Notch signaling and tip cell filopodia formation in mice, indicating that Müller cells make a more important contribution to retinal angiogenesis than generally appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Moreover, increased VEGF expression in Mü ller cells under hyperglycemic conditions is one of the major contributors to pathological intraocular neovascularization. 11,12 Therefore, exposing the potential mechanism of glucoseinduced VEGF expression in Mü ller cells is essential to reveal the underlying neovascularization in diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal Müller cells are the principal supporting cells in the neural retina and participate in retinal angiogenesis, neural protection and other physiological functions [15,16]. Recent studies have indicated that HIF-1α is produced in all of the retinal layers [17].…”
Section: Introductionmentioning
confidence: 99%